Impact of Instructional Materials Toward Integrating Children with Learning Difficulties in Islamic Primary Schools - Ahmad Garba (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
From an educational perspective, there are special differences between people, every student, whether a child or an adult, has specific educational needs that distinguish him from his peers of the same age, which necessitates designing the curriculum according to these differences, and these needs, and equipping the student with special attention, which is known as special education, through caring for those with special needs, such as health, psychological and social, rehabilitation and professional, and educational. one of the most important things that must be focused on in qualifying students with learning difficulties are skills, it could be a communication or social skills, which are the basis for obtaining other skills, as humans are social by nature. and he cannot master other skills without it, as person's interacts with his environment through good communication, he obtains many things and achievements, and other skills such as cognitive skills and self-care skills, and many skills that students with learning difficulties need. to achieve this, an integrated educational program was established, this program aims to increase the opportunities for social and educational interaction between students with special needs - learning difficulties - and regular students. This program is known as academic integration, which is a positive trend towards the participation of regular students and others in one class. This integration works to place the child with special needs in the regular class with regular students for some time and in some subjects, which makes a child benefits from, provided that the appropriate conditions are available for the success of this trend. There is also another program, which is social integration, which is the final stage in developing special education programs for those with learning difficulties, because it helps positively to those with special needs from members of society, and this is represented in the field of work by providing suitable job opportunities for them as members of society. on this basis, this paper aims to discuss on the impact of Impact of instructional materials toward integrating children with learning difficulties in Islamic primary schools in Nigeria, a descriptive research design was used, and the results of the research indicate that instructional materials have a significant impact on enhancing educational achievements of children with learning difficulties, and also helps in integrating them academically to compete with their colleagues.